Development of a food product profile for boiled and steamed sweetpotato in Uganda for effective breeding - Mwanga, Robert O.M.; Mayanja, S.; Swanckaert, J.; Nakitto, M.; Felde, T. zum; Grüneberg, W.J.; Mudege, Netsayi N.; Moyo, M.; Banda, L.; Tinyiro, S.E.; Kisakye, S.; Bamwirire, D.; et al. (Wiley, 2021)
This study sought to understand user preferences of raw, boiled and steamed sweetpotato, a staple food in Uganda. A sequential methodology involving state of knowledge review, gendered food mapping, processing diagnosis and consumer testing was used in Lira and Kamwenge districts. Preferred raw sweetpotato characteristics were large roots (≥ 3 cm diameter) with a sweet taste, smooth skin and hard texture, while mealiness, sweet taste and good sweetpotato smell were important attributes for boiled sweetpotato. Processors, mostly women, highlighted ease of peeling and sappiness of raw roots. There were gender differences in quality characteristic preferences and perceived importance. The released variety, NASPOT 8, had the highest overall liking in Kamwenge and was well liked in Lira. Penalty analysis of consumer data showed that sweetness and firmness were key drivers of overall liking. The results will support breeding programmes in meeting specific end‐user product profiles, selection criteria and uptake of new varieties.